The doomsday conspiracy - Sheldon, Sidney (New York : Morrow, 1991)
Navy Commander Bellany is assigned to investigate the crash of a weather balloon in the Swiss Alps. However, for him it is also the beginning of a journey of terror into the incomprehensible.
Keywords: English fiction